2004
DOI: 10.1093/ajcn/80.6.1618
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus induces peripheral hyporesponsiveness in stimulated CD4+ T cells via modulation of dendritic cell function

Abstract: We propose that L. rhamnosus modulates DC function to induce a novel form of T cell hyporesponsiveness; this mechanism might be an explanation for the observed beneficial effects of probiotic treatment in clinical disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(136 citation statements)
references
References 34 publications
9
119
0
7
Order By: Relevance
“…We, however, did not find any significant changes in bacteria-induced production of cytokines apart from the TNF-α in the PBMC cultures of our study subjects after L. rhamnosus GG treatment. In another study with healthy adults and with patients with Crohn's disease, L. rhamnosus GG decreased the production of IL-2, IL-10 and IL-4 from PBMCs sorted as naïve and memory T cells [33] . It seems that L. rhamnosus GG has a role in modulating the cytokine responses and may possess an anti-inflammatory potential in healthy individuals.…”
Section: Discussionmentioning
confidence: 90%
“…We, however, did not find any significant changes in bacteria-induced production of cytokines apart from the TNF-α in the PBMC cultures of our study subjects after L. rhamnosus GG treatment. In another study with healthy adults and with patients with Crohn's disease, L. rhamnosus GG decreased the production of IL-2, IL-10 and IL-4 from PBMCs sorted as naïve and memory T cells [33] . It seems that L. rhamnosus GG has a role in modulating the cytokine responses and may possess an anti-inflammatory potential in healthy individuals.…”
Section: Discussionmentioning
confidence: 90%
“…rhamnosus) was shown to modulate DC function to induce a novel form of T-cell hyporesponsiveness [97]. Another study in mice demonstrated that the probiotic preparation VSL #3 increased the expression of B7.1 (CD80), B7.2, CD40 and MHC class II molecules.…”
Section: Activation Of Tolerogenic Dendritic Cells (Dcs)mentioning
confidence: 99%
“…Lactobacillus rhamnosus GG decreased T cell proliferation and cytokine production, especially of IL-2, IL-4 and IL-10, such as demonstrated in CD3 ⁄ CD28-stimulated T cells derived from dendritic cells matured in the presence of Lact. rhamnosus GG (Braat et al 2004). However, bacterial cell components involved in the modulatory properties of Lact.…”
Section: Introductionmentioning
confidence: 99%